RATING ASSESSMENT OF THE ACTIVITY OF COMMERCIAL BANKS BRANCHES - Rajabov Behzod Mirshodovich (American Journals, 2024)
In the market of banking services, it is important to increase the sales of services by expanding business and organizing branch activities. Evaluating the activities of bank branches and coordinating their activities is one of the important and urgent tasks of bank management. It is important to identify the branches of the bank that have achieved good results and those that are lagging behind the average indicators and to take measures to improve their performance. This leads to the need to create a system for evaluating the activities of bank branches and divisions. However, it requires the use of accurate evaluation methods to identify branches that are lagging behind due to management inefficiency, mislocation, and other aspects. The rating and rating system allows for a systematic analysis of branch activities, identification of negative factors affecting their activity, and identification of leading and lagging units. This article examines the issues of using the rating evaluation system in the activities of the branches of the banks of the Republic of Uzbekistan and makes recommendations for its improvement.
Keywords: Bank branch, rating, rating evaluation, profit per employee, income, cost, net profit, efficiency, interest income, non-interest income, asset efficiency, capital efficiency, net interest margin.